Deradicalisation Regulations and Violation of Human Rights: A Few Instances from China and Sri Lanka (Dhaka University Law Journal, 2022)
Given the gravity of crimes of violent extremism and the heightened securitisation associated with it, preventive or counter-terrorism measures have often led to the abuse of power,infringement of justice, and polarisation in the society. As part of countering terrorism,‘deradicalisation’ regulations and practices need to affirm the protection and promotion of human rights. Unfortunately, though this was a consistent proposition by the United Nations (UN), several nations have failed to observe human rights monitoring in their designated ‘deradicalisation’ regulations. This paper, relying on the secondary scholarships and reports of media, the UN and other human rights organisations, has reviewed how states may violate the human rights of the members of targeted communities under the disguise of ‘deradicalisation’. In this regard, the paper has used a few instances from China and Sri Lanka to illustrate the matter more precisely. The objective of the article is to highlight how a lack of theorisation of human rights in deradicalisation may lead countries to end up with politically motivated ‘deradicalisation’ frameworks that contradict UN mandate and other national and international human rights safeguards.Dhaka University Law Journal, 2022, 33(1), 57-72